DIALEKTIKA ALAM DAN MASYARAKAT : ANALISIS GEOGRAFI CAMPING GROUND TRAWAS SEBAGAI POTENSI OUTDOOR LEARNING - Vadhliyati Maulida; Alifia Putri Nasywa Az Zahra; Farah Diana; Farah Zahidah Ayyasyi; Muhammad Rafly Firmansyah; Dhimas Bagus Virgiawan (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
This study aims to analyze the dialectic between natural conditions and community dynamics in shaping the potential of the Alas Veenuz Trawas Camping Ground as a model of social-geography learning based on outdoor learning. The study employed a descriptive quantitative approach with data collection techniques consisting of field observation, questionnaire distribution, and in-depth interviews with site managers and visitors. Physical condition measurements were carried out through zoning analysis, air temperature and elevation measurements, and Temperature Humidity Index (THI) calculations across four functional zones. The results indicate that all zones exhibit comfortable thermal conditions, with temperatures ranging from 24-26°C, well below the tropical THI discomfort threshold of 27°C. Questionnaire analysis revealed an overall mean score of 4.35 (very high category) across all indicators: location (4.41), spatial interaction (4.31), utility value (4.39), and accessibility (4.29). The physical geographical characteristics combined with community social dynamics form an authentic and contextual learning ecosystem. The dialectic between nature and society contributes significantly to the potential of Alas Veenuz as an integrative, sustainable, socially-grounded outdoor learning model, worthy of further development as an environment-based educational laboratory. ABSTRAK Penelitian ini bertujuan untuk menganalisis dialektika antara kondisi alam dan dinamika masyarakat dalam membentuk potensi Camping Ground Alas Veenuz Trawas sebagai model pembelajaran geografi-sosial berbasis outdoor learning. Penelitian menggunakan pendekatan kuantitatif deskriptif dengan teknik pengumpulan data berupa observasi lapangan, penyebaran kuesioner, dan wawancara mendalam kepada pengelola serta pengunjung kawasan. Pengukuran kondisi fisik dilakukan melalui analisis zonasi, pengukuran suhu udara, ketinggian elevasi, serta perhitungan Temperature Humidity Index (THI) pada empat zona fungsional. Hasil penelitian menunjukkan bahwa seluruh zona berada dalam kondisi termal nyaman dengan suhu antara 24-26°C, jauh di bawah ambang ketidaknyamanan THI tropis sebesar 27°C. Hasil kuesioner menunjukkan skor rata-rata 4,35 (kategori sangat tinggi) pada seluruh indikator: lokasi (4,41), interaksi keruangan (4,31), nilai guna (4,39), dan aksesibilitas (4,29). Karakteristik geografis fisik berpadu dengan dinamika sosial masyarakat membentuk ekosistem pembelajaran autentik. Dialektika alam dan masyarakat berkontribusi signifikan terhadap potensi Alas Veenuz sebagai model outdoor learning berbasis geografi-sosial yang integratif, berkelanjutan, dan layak dikembangkan sebagai laboratorium pendidikan berbasis lingkungan.